Nerve Block Use after Hip Fracture Versus Elective Hip or Knee Arthroplasty: Retrospective Analysis. Issue 4 (3rd March 2020) - Neuman, Mark D.; Elkassabany, Nabil M.; Ochroch, Jason; Newcomb, Craig; Brensinger, Colleen; Mehta, Samir; Gaskins, Lakisha J.; Lane‐Fall, Meghan B.
Abstract : OBJECTIVES: Although peripheral nerve blocks are associated with improved pain control and end outcomes among older adults with hip fracture, their current utilization among US hip fracture patients is not well understood. We characterized contemporary use of peripheral nerve blocks after hip fracture over time and identified predictors of nerve block receipt. DESIGN: Retrospective cohort study of claims data from one large national private US insurer. SETTING: US acute care hospitals. PARTICIPANTS: A total of 94 985 adults aged 50 years and older hospitalized for a femoral neck, intertrochanteric, or subtrochanteric fracture; 409 263 adults aged 50 years and older hospitalized for elective hip or knee arthroplasty between 2004 and 2016. MEASUREMENTS: Receipt of a peripheral nerve block for pain control, based on Current Procedural Terminology codes in physician service claims. RESULTS: Overall, 2874 hip fracture patients (3.0%; 95% confidence interval [CI] = 2.9‐3.1) received a nerve block for pain control, and the percentage receiving a block increased from .4% in 2004‐2006 (95% CI = .3%‐.6%) to 4.6% in 2013‐2016 (95% CI = 4.4%‐4.8%; P  < .001). The adjusted odds of receiving a nerve block was lower for patients with vs without dementia (odds ratio [OR] = .88; 95% CI = .80‐.98; P = .02) and among patients aged 75 to 84 vs 64 years or younger (OR = .86; 95% CI = .74‐1.00; P = .02). The odds of nerve block receipt did not vary according to race, ethnicity, fracture location, or most other common comorbidities. Compared with patients with hip fracture, the adjusted odds of nerve block receipt were 2 times higher among patients undergoing elective hip replacement and more than 30 times higher among patients undergoing elective knee replacement. CONCLUSION: Although use of peripheral nerve blocks for pain control after hip fracture has increased over time, fewer than 5 of every 100 patients hospitalized with hip fracture currently receive a peripheral nerve block, suggesting possible underuse. J Am Geriatr Soc 68:835–840, 2020 Abstract : See related Editorial by Ellen F. Binder